Morphometric Characterization and Zoometric Indices of High-Andean Creole Cows from Southern Peru - Ccalta Hancco, Ruth (2025)
High-Andean Creole cattle represent a genetic resource with significant adaptive value in high-altitude ecosystems. In this study, 151 Creole cows from the provinces of Canas and Quispicanchis (Cusco, Peru) were evaluated to characterize their morphometry, calculate zoometric indices, and establish functional biotypes. Ten morphometric parameters were measured, and eight structural indices were calculated. Four differentiated biotypes were identified through the multivariate analysis and hierarchical clustering of quantitative variables (BI, BII, BIII, and BIV). Morphological differences were statistically significant (p < 0.05) and associated with different productive orientations. Biotype I showed greater thoracic development and a compact structure, which is compatible with intermediate beefaptitude; Biotype II exhibited more elongated proportions and a lower weight, indicating a dairy tendency; Biotype III stood out for its muscle mass, thoracic depth, and pelvic width, evidencing a clear beef orientation; and Biotype IV combined a higher weight, rectangular conformation, and wide pelvis, showing potential for beef production and ease of calving. Functional differentiation was supported by Principal Coordinates Analysis (PCoA) and PERMANOVA tests. Correlations between morphometric variables and zoometric indices revealed anatomical patterns consistent with the productive functions proposed. The results highlight the morpho-functional diversity of Andean Creole cattle and their potential for conservation and improvement programs in extensive highland systems.